EFFECTS OF EXPERT SYSTEMS IN COMPUTER BASED SUPPORT FOR CMMI IMPLEMENTATIONS - (:unkn) unknown (SCITEPRESS, 2010)
Computing systems are becoming more complex in very dynamic and uncertain situations. Due to this complexity, the importance of process focused quality approaches is increasing. Capability Maturity Model Integration (CMMI) standards and implementation practices were developed to simplify the software project management and to assure expected quality of the respective software. Realizing the CMMI systems, building and monitoring the implementation practices require an extensive knowledge and experience. Organizations receive these mainly through consultants which may become too costly in most of the cases. Although there have been some computer based support tools available in the market, those still require human experts to justify the related artifacts. In this study a knowledge-based assistant system so called CMMI Assistant is introduced. The main aim of this tool is to support CMMI implementations through utilising expert system methodology.
Keywords: CMMI; Knowledge based System; Expert System; Software Quality; TRENSIM; Train Simulator